Liver Transplantation and Development of Diabetes in an Adolescent Male With HNF1B Disease. Issue 3 (25th August 2021) - Weckwerth, Jody A.; Dahl, Amanda R.; Pittock, Siobhan T.; Kumar, Seema; Rosen, Charles B.; Grothe, Rayna M.; Furuya, Katryn N.
Abstract : Mutations in the hepatocyte nuclear factor-1-beta ( HNF1B ) gene cause a variety of diseases in different organ systems. Mutations have been described as causing neonatal cholestasis, maturity-onset diabetes of the young (type 5), cortical renal cysts, urogenital abnormalities, liver dysfunction, and atrophy of the pancreas. We describe a male patient who presented with cholestatic liver disease in infancy which progressed by age 14 to end-stage liver disease due to HNF1B disease. He subsequently underwent liver transplantation at age 15 and then developed diabetes requiring insulin which did not resolve after cessation of corticosteroids. To our knowledge, this is the first case reported of liver transplantation for decompensated cirrhosis secondary to HNF1B disease.